OT제어망에서 다중 제어시스템 접근통제용 공개키 기반 운용자 인증 방안 - 김대휘(Dae-Hwi Kim); 조인준(In-June Jo) (한국콘텐츠학회 논문지, 22(9), 2022)
The method of accessing multiple control systems in the OT control network centered on operation technology uses the operator authentication technology of each control system. An example is ID/PW operator authentication technology. In this case, since the OT control network is composed of multiple control systems, operator authentication technology must be applied to each control system. Therefore, the operator must bear the inconvenience of having to manage authentication information for each control system he manages. To solve these problems, SSO technology is used in business-oriented IT networks. However, if this is introduced into the OT control network as it is, the characteristics of the limited size of the OT control network and rapid operator authentication are not reflected, so it cannot be seen as a realistic alternative. In this paper, a public key-based authentication mechanism was newly proposed as an operator authentication technology to solve this problem. In other words, an integrated public key certificate that applies equally to all control systems in the OT control network was issued and used to access all control systems, thereby simplifying the authentication information management and making access to the control system more efficient and secure. 운용기술 중심의 OT제어망내의 다중 제어시스템들에 접근하는 방법은 각각의 제어시스템이 제공하는 운용자 인증기술을 사용한다. 그 예로 ID/PW 운용자 인증기술을 들 수 있다. 이 경우 OT제어망은 다중 제어시스템으로 구성되기 때문에 각각 제어시스템별로 운용자 인증기술이 적용되어야 한다. 따라서 운용자는 자신이 관리하는 제어시스템별로 인증정보를 관리해야 하는 불편을 감수해야한다. 이러한 문제 해결을 위해 비즈니스 중심의 IT망에서는 SSO기술을 사용한다. 하지만, 이를 OT제어망에 그대로 도입할 경우 OT제어망의 제한된 규모 및 신속한 운용자 인증 등의 특성이 반영되지 않아 현실적인 대안으로 볼 수 없다. 본 논문에서는 이러한 문제를 해결하고자 운용자인증기술로 공개키 기반 인증방안을 새롭게 제안하였다. 즉, OT제어망내의 모든 제어시스템들에 동일하게 적용되는 하나의 통합 공개키 인증서를 발행하고 이를 모든 제어시스템에 접근할 경우 활용함으로써 운용자의 인증정보관리의 단순화 및 제어시스템에 접근을 보다 효율적이고 안전하게 하였다.